Analisis Karakteristik Hujan Ekstrim Untuk Mendukung Pengembangan Peringatan Dini Lahar Dingin di Lereng Gunung Merapi - Iryani , S.Y. (Civil Engineering Department, Tadulako University, 2020)
Mt. Merapi cold lava disasters in 2010 had caused a lot of public infrastructure and facilities in the area around Mt. Merapi were damaged, due to the occurrence of debris flows triggered by extreme rainfall. Analysis of extreme rainfall characteristics are conducted to determine the pattern of distribution of the amount of hourly rainfall in the slopes of Mt. Merapi. To reduce the negative impact caused by cold lava flood, it is necessary to plan an Early Warning System (EWS) and the proper evacuation measures. EWS based Rainfall intensity, can refer to the Critical Line Curve. The research results showed the greatest rainfall intensity occurred in the Mt. Maron station Pwith the cumulative relative frequency of rainfall intensity >20 mm/hr in between the years 1988 to 2010 with 6.74%. Analysis of the incidence of the most extreme hourly rainfall of 14 rainfall stations in the slopes of Mt. Merapi in 1988 to 2010 occurred in kemasan station in 2010 with 621.5 mm in January at 6:00 p.m. to 7:00 p.m. Critical Line Curve Kali Gendol rain station Batur, Deles and Sorosan, non-causing rainfall in the dangerous area is 24 events (13.79%), causing rainfall in the dangerous area is 4 events (2.30%) and non-causing rainfall in the safety area is 146 events (83.91%). Cumulative Relative frequency rainfall intensity >20 mm/hr at rainfall stations close to the Kali Gendol i.e. Batur, Deles and Sorosan rainfall station from the highest to the lowest are 2.74%, 2.33% and 1.70%, respectively.